George Washington and the general's dog - Murphy, Frank, 1952-; Walz, Richard (New York : Random House, 2004)
Recounts events in the life of George Washington which focus on his fondness for animals.
G2
Keywords: Washington, George, -- 1732-1799 -- Juvenile literature; Washington, George, -- 1732-1799.; Presidents -- United States -- Biography -- Juvenile literature; Generals -- United States -- Biography -- Juvenile literature; Dogs -- United States -- History -- 18th century -- Juvenile literature; Human-animal relationships -- United States -- History -- 18th century -- Juvenile literature; Presidents; Human-animal relationships